2001
DOI: 10.1023/a:1009842501113
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to describe the basic mathematical proficiency and the medication calculation skills of graduating nursing students in Finland. A further concern was with how students experienced the teaching of medication calculation. We wanted to find out whether these experiences were associated with various background factors and the students' medication calculation skills. In spring 1997 the population of graduating nursing students in Finland numbered around 1280; the figure for the whole year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 19 publications
0
1
0
3
Order By: Relevance
“…There is substantial evidence that nurses and nursing students perform badly when tested in medication calculations (Fleming et al, 2014;Grandell-Niemi et al, 2001;Simonsen et al, 2014;Wright, 2010). One study that measured numerical and drug calculation abilities found that 92% of nursing students and 89% of registered nurses failed the drug calculation test (McMullan et al, 2010).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…There is substantial evidence that nurses and nursing students perform badly when tested in medication calculations (Fleming et al, 2014;Grandell-Niemi et al, 2001;Simonsen et al, 2014;Wright, 2010). One study that measured numerical and drug calculation abilities found that 92% of nursing students and 89% of registered nurses failed the drug calculation test (McMullan et al, 2010).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Hemşirenin ilaç uygulamalarını doğru şekilde yapabilmesinde yeterli teorik bilgiye, ilaç dozu hesaplama becerisine ve yeterli klinik deneyime sahip olması en önemli gerekliliklerdendir. [15,16] İlgili literatür incelendiğinde, hemşirelik öğrencileriyle yapılan çalışmala- rın oldukça az olduğu ve yapılan çalışmaların da öğrencilerin doz hesaplama becerileri ve klinik alanda yaptıkları hatalar üzerine yoğunlaştığı görülmektedir. [17][18][19][20] Örneklem grubu farklı olmakla birlikte Küçükakça ve Özer [21] (2016) cerrahi kliniklerde çalışan hemşirelerle yaptıkları çalışmalarında, hemşirelerin (%43.6) yüksek riskli ilaçlarla ilgili bilgi düzeylerinin düşük olduğunu bildirmiştir.…”
Section: Discussionunclassified
“…Çalışmamızda öğrencilerin %76'sının birinci, %96'sının ikinci klinik uygulama sınavında doz hesaplama problemini hatasız yaptıkları belirlendi. Grandell-Niemi, Hupli ve Leino-Kilpi [26] (2001) Finlandiya'da mezun olmak üzere olan 180 hemşirelik öğrencisinin ilaç dozu hesaplama becerilerini incelemişlerdir. Öğrencilerin %70'inin ilaç dozu hesaplama becerilerinde kendisini yeterli hissettiğini ve %22'sinin ilaç doz hesabını hatalı yaptığı tespit edilmiştir.…”
Section: Discussionunclassified
“…[23] Hesaplanan ilaç dozunun enjektöre doğru çekilmesi becerisinin kazandırılması da ele alınması gereken bir konudur. Ancak yapılan çalışmalarda [3,[24][25][26][27][28] bu konu hemşirelere ya sözel olarak sorulmuş ya da doz hesabı yapıp yapamadığı incelenmiştir. Bu çalışmada öğrencilerin doz hesabı yapabilmesinin yanında, yazılı sınav kâğıdına çizilmiş olarak verilen enjektörler üzerinde yaptıkları işaretlemeler üzerinden, enjektöre doğru doz ilacı çekip çekemedikleri incelenmiştir.…”
unclassified